Ultra-estrutura de glândulas abdominais tegumentares em Oxaea flavescens (Hymenoptera, Andrenidae, Oxaeinae) - Guerino, Adriane Cristina [UNESP]; Da Cruz-Landim, Carminda [UNESP] (FapUNIFESP (SciELO), 2002)
The sternal glands of the abdomen of Oxaea flavescens (Klug, 1807) consist of class III glandular cells around a reservoir constituted by branched folds of the intersegmental membrane of segments III, IV and V. The gland cells are rich in rough endoplasmic reticulum and produce a secretion with mucous aspect. The treatment with oxidated osmium and ruthenium red showed numerous Golgi regions in the cell and carbohydrates absorption from the haemolymph, respectively. The high degree of development of the glands suggests an important function to the species, although still unknown.
Ultrastructure of abdominal tegumentar glands in Oxaea flavescens (Hymenoptera, Andrenidae, Oxaeinae)
Keywords: Exocrine glands; Oxaea; Sternal glands; Tegumentary glands